Correlation analysis of vaginal microecology and different types of human papillomavirus infection: a study conducted at a hospital in northwest China - Feng, Fang; Hou, Yue-min; Zhang, Yan; Wang, Lu-yuan; Li, Pei-pei; Guo, Ying; An, Rui-fang (Frontiers in Medicine, 2023)
Background: Vaginal microecology has a definite influence on human papillomavirus (HPV) infection and clearance, but the specific correlation is still controversial. This research aimed to investigate differences in the vaginal microenvironment of different types of HPV infection and also provide data supporting clinical diagnosis and treatment. Methods: According to strict inclusion and exclusion criteria, the case data of 2358 female patients who underwent vaginal microecology and HPV-DNA tests at the same time in a hospital from May 2021 to March 2022 were retrospectively analyzed. The population was divided into HPV positive group and HPV negative group. HPV positive patients were further classified into HPV16/18 positive group and HPV other subtypes positive group. The vaginal microecology of HPV-infected patients was analyzed using the Chi-square test, Fisher’s exact test, and logistic regression. Results: Among the 2358 female patients, the HPV infection rate was 20.27%(478/2358), of which the HPV16/18 infection rate was 25.73%(123/478) and the HPV other subtypes infection rate was 74.27%(355/478). The difference in HPV infection rates between age groups was statistically significant. The prevalence of mixed vaginitis was 14.37%(339/2358), with bacterial vaginosis (BV) paired with aerobic vaginitis accounting for the majority (66.37%). The difference in HPV infection rates among mixed vaginitis was not statistically significant. The prevalence of single vaginitis was 24.22%(571/2358), with the most frequent being vulvovaginal Candidiasis (VVC)(47.29%, 270/571), and there was a significant difference in HPV infection rates among single vaginitis. Patients with BV had a higher risk of being positive for HPV16/18 (OR:1.815,95%CI:1.050–3.139) and other subtypes (OR:1.830,95%CI:1.254–2.669). Patients with Trichomoniasis vaginitis (TV) were at higher odds of other HPV subtype infections (OR:1.857,95%CI:1.004–3.437). On the contrary, patients with VVC had lower odds of becoming infected with other HPV subtypes (OR:0.562,95%CI:0.380–0.831). Conclusion: There were disparities in HPV infection among different age groups; therefore, we should pay attention to the prevention and treatment of susceptible individuals. BV and TV are linked to HPV infection, hence, restoring the balance of vaginal microecology could assist in the prevention of HPV infection. As a protective factor for other HPV subtype infections, VVC may provide new insights for the development of immunotherapeutic therapies.